Effectiveness of Group Investigation Cooperative Learning Method Based on Curipod Application For Class II Students At MTs Uswatun Hasanah - Nurhalimah; Surya Bakti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Abstrak Penelitian ini bertujuan menganalisis efektivitas penerapan metode kooperatif tipe Group Investigation dalam meningkatkan hasil belajar Pendidikan Agama Islam pada siswa kelas II MTs Uswatun Hasanah. Penelitian menggunakan pendekatan penelitian tindakan kelas dengan subjek sebanyak 39 siswa. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam hasil belajar siswa setelah penerapan metode Group Investigation. Rata-rata nilai pre-test awal sebesar 36,63, dengan tidak ada siswa yang mencapai Kriteria Ketuntasan Minimal. Setelah siklus I dengan metode konvensional, 21,4% siswa mencapai Kriteria Ketuntasan Minimal, sedangkan pada siklus II setelah penerapan metode kooperatif tipe Group Investigation, persentase siswa yang mencapai Kriteria Ketuntasan Minimal meningkat menjadi 89,48%. Temuan ini menunjukkan bahwa metode kooperatif tipe Group Investigation efektif meningkatkan hasil belajar Pendidikan Agama Islam siswa. Oleh karena itu, metode ini direkomendasikan untuk digunakan dalam proses pembelajaran guna meningkatkan prestasi siswa. Kata Kunci: Metode kooperatif, Group Investigation, hasil belajar, Pendidikan Agama Islam, penelitian tindakan kelas. Abstract This study aims to analyze the effectiveness of the cooperative learning method, specifically the Group Investigation type, in improving learning outcomes in Islamic Religious Education for second-grade students at MTs Uswatun Hasanah. This research employed a classroom action research approach involving 39 students as subjects. The results showed a significant improvement in students' learning outcomes after applying the Group Investigation method. The initial pre-test average score was 36.63, with no students meeting the Minimum Mastery Criteria. After the first cycle using conventional methods, 21.4% of students met the Minimum Mastery Criteria, which increased to 89.48% after the second cycle using the Group Investigation cooperative method. These findings indicate that the Group Investigation cooperative learning method is effective in enhancing students' learning outcomes in Islamic Religious Education. Therefore, this method is recommended for use in the learning process to improve student achievement. Keywords: Cooperative learning, Group Investigation, learning outcomes, Islamic Religious Education, classroom action research.